PbI2 3D network transporting model for the charge separation mechanism of PbSe detectors. Issue 58 (17th November 2021) - Shi, Kanghao; Liu, Yun; Luo, Yingmin; Bian, Jiming; Qiu, Jijun
Abstract : As the transporting channels for the photogenerated electrons, the integrity and densification of the PbI2 3D network structure distributed in the interfaces between PbSe crystalline grains dominates the performances of PbSe detectors. Abstract : PbSe films deposited by chemical bath deposition (CBD) technology were sensitized in various atmospheres to distinguish the role of iodine and oxygen in the sensitization process. No infrared (IR) photo response was observed in samples sensitized in pure oxygen, showing the O element cannot trigger the infrared response of PbSe. However, a high detectivity of 1 × 10 10 was achieved in the sample sensitized in a N2 /I2 atmosphere, which demonstrates iodine is a key element for inducing an IR response. The role of iodine was analyzed from the morphological evolution, phase composition transformation and resistance change during the sensitization process. The XRD and FESEM results show a PbI2 3D network forming around the PbSe grains in the sensitization process, playing the role of photo-generated electron transporting channels, which is key to inducing the IR response of PbSe detectors. The 3D network conducting model can explain well the charge separation mechanism of PbSe IR photoconductive detection.